The influence of very small magnetic fields on radical recombination reactions in the limit of slow recombination - Till, U; Timmel, C; Brocklehurst, B; Hore, P (1998)
A magnetic field can modify the recombination probability of pairs of free radicals even though it may be weaker than the local magnetic (hyperfine) interactions of the unpaired electrons. For a radical pair born in an electronic singlet state, there is a remarkably simple and general relation between the (singlet) recombination yield ΦS in zero field and in the presence of a weak field, when the recombination is very slow. The magnitude of ΦS at zero field in excess of its statistical value of one quarter is simply three times that in a weak field. The origin of this relation and the conditions under which it is obeyed are explored.